2015
DOI: 10.1371/journal.pone.0121764
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Octameric Structure Affects Plasminogen-Binding Capacity of Streptococcal Enolase

Abstract: Group A Streptococcus (GAS) is a human pathogen that has the potential to cause invasive disease by binding and activating human plasmin(ogen). Streptococcal surface enolase (SEN) is an octameric α-enolase that is localized at the GAS cell surface. In addition to its glycolytic role inside the cell, SEN functions as a receptor for plasmin(ogen) on the bacterial surface, but the understanding of the molecular basis of plasmin(ogen) binding is limited. In this study, we determined the crystal and solution struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 64 publications
2
40
0
Order By: Relevance
“…A structure model of SEN based on the crystal structure of GAS and S. pneumoniae α-enolase indicates that SEN forms an octameric structure comprising a tetramer of dimer 22 36 37 . These models show that lysine residues of SEN at positions 252 and 255 within a unique lysine-rich PLG-binding motif are located in a surface-exposed loop at the edge of the toroidal octameric protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A structure model of SEN based on the crystal structure of GAS and S. pneumoniae α-enolase indicates that SEN forms an octameric structure comprising a tetramer of dimer 22 36 37 . These models show that lysine residues of SEN at positions 252 and 255 within a unique lysine-rich PLG-binding motif are located in a surface-exposed loop at the edge of the toroidal octameric protein.…”
Section: Discussionmentioning
confidence: 99%
“…Internal lysine residues in the closely related α-enolase of S. pneumoniae have also been reported to play crucial roles not only in the acquisition of PLG, but also in their virulence in a mouse infection model 38 . Recent structural and biophysical analyses of GAS SEN demonstrated that mutations in the minor inter-subunit interface induce destabilization of the octameric structure, thereby promoting the accessibility of PLG to its binding sites 37 . Since C-terminus lysine residues are located in the minor interface, we speculated that mutations in this region cause a conformational change of SEN, which might facilitate interaction of PLG with internal PLG-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…The X-ray crystal structure of Str enolase has recently been deposited in the data bank (3ZLH.PDB Fig 1 ). The coordinates were kindly given to us by the authors (Cork, Ericsson, Law, Casey, Valkov, Bertozzi, Stamp, Aquilina, Whisstock, Walker and Kobe) [ 22 ]. This protein contains one mutation (E77K) relative to the Str enolase DB.…”
Section: Resultsmentioning
confidence: 99%
“…There has been a significant amount of work done on mutant forms of enolase from Streptococcus pyogenes and Streptococcus pneumoniae [ 7 , 8 , 22 , 33 35 ]. Cork et al [ 22 ] recently found that changing K362 to alanine destabilizes the Str enolase. Much of the rest of the above cited work was aimed at determining the role of specific residues, especially residues 434 and 435, in the binding of plasminogen.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction with KR1 and KR5 domains of Plg occurs through lysine residues located at the C-terminal end of enolase, as well as on another internal binding site. Plg undergoes a conformational change to expose the cut site for PAs in order to induce Plm formation [ 144 ].…”
Section: Plg–enolase Interactionmentioning
confidence: 99%